Production of biodiesel by ozonation of coconut oil - Cabang, Romulo Gonzales (2007)
This study investigated production of biodiesel by ozonation of coconut oil. Its specific objectives were to determine the change in the physical and chemical properties of coconut oil during ozonation, to determine the effect of temperature on the process, and to determine if the process produces biodiesel of acceptable characteristics (Philippine National Standards). Three ozonation experiments were conducted at different temperature conditions: ambient (30 deg.C), 40 and 50 deg.C. The density, kinematic viscosity, heating value, pour point, cloud point, flash point, total and free glycerin were measured at different ozonization time. Fourier Transform - Infrared (FT-IR) spectroscopy was used to determine changes in the composition of biodiesel during ozonation and gain insight about the chemical reactions occuring during ozonation.Two-hours ozonation at ambient temperature (30 deg.C) rendered a smaller change in most of the properties, i.e. density, viscosity, heating value, cloud and flash points, free and total glycerin. An exception to this was pour point, which decreased from 14 to 9 deg.C. The changes were greater at 40 and 50 deg.C. the most pronounced changes in the coconut oil were the increase in density, decrease in kinematic viscosity. at 40 deg.C and 50deg.C, FT-IR spectroscopy results indicated that absorbance of C-H, C-O and C=O bonds generally decreased as ozonation time increased. This implies that ozone caused the bonds of molecules to break likely resulting in smaller molecules. This explains the decrease in kinematic viscosity. The changes in number of these bonds at 30 deg.C ozonation were not as high as those at 40 and 50 deg.C. The best properties of ozonized coconut oil were exhibited at 40 deg.C. The total glycerin after ozonation was higher than the standard maximum value, hence, a process to remove this is necessary. Kinematic viscosity, flash point and free glycerin content were within standard values while pour point and cloud point were still higher at maximum values.